Diagnostics in skeletal muscle channelopathies - Vicino, Alex; Brugnoni, Raffaella; Maggi, Lorenzo (Expert review of molecular diagnostics, 2023)
Skeletal muscle channelopathies (SMCs) are a heterogenous group of disorders, caused by mutations in skeletal ion channels leading to abnormal muscle excitability, resulting in either delayed muscle relaxation (myotonia) which characterizes non-dystrophic myotonias (NDMs), or membrane transient inactivation, causing episodic weakness, typical of periodic paralyses (PPs). SMCs include myotonia congenita, paramyotonia congenita, and sodium-channel myotonia among NDMs, and hyper-normokalemic, hypokalemic, or late-onset periodic paralyses among PPs. When suspecting an SMC, a structured diagnostic approach is required. Detailed personal and family history and clinical examination are essential, while neurophysiological tests should confirm myotonia and rule out alternative diagnosis. Moreover, specific electrodiagnostic studies are important to further define the phenotype of de novo cases and drive molecular analyses together with clinical data. Definite diagnosis is achieved through genetic testing, either with Sanger sequencing or multigene next-generation sequencing panel. In still unsolved patients, more advanced techniques, as exome-variant sequencing or whole-genome sequencing, may be considered in expert centers. The diagnostic approach to SMC is still mainly based on clinical data; moreover, definite diagnosis is sometimes complicated by the difficulty to establish a proper genotype-phenotype correlation. Lastly, further studies are needed to allow the genetic characterization of unsolved patients.